Imatinab mesylate treatment in Chronic Myeloid Leukemia (CML)- understanding the fundamental pharmacokinetic and pharmacogenetic mechanisms for variation in response - Ankathil, Ravindran (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2016)
Although lmatinib mesylate (IM) is the gold standard drug for Chronic Myeloid Leukemia (CML) treatment, resistance to IM emerges in a significant number of patients. Resistance could be due to several factors. Pharmacokinetic variability as a result of genetic polymorphisms in IM metabolizing genes could be a potential factor. This study was undertaken to investigate the genotype frequencies and the impact of ORM1 520G>A, PXR 1792A>G, CAR 540C>T, CYP3A4 878T>C and CYP3A5 6986A>G polymorphisms towards CML susceptibility risk and IM response. A total of 540 subjects (270 CML patients and 250 normal healthy controls) have been recruited in this study. Genotyping was performed and the association between allelic variants and CML susceptibility risk and response to IM treatment were assessed by means of odds ratio (OR) with 95% confident interval s calculated by logistic regression. Results showed that PXR 1792A>G, CAR 540C>T and CYP3A5 6986A>G were significantly associated with IM responses and CAR 540C>T, CYP3A4 878T>C and CYP3A5 6986A>G were significantly associated with CML susceptibility risk. Further study should be done on a larger scale to validate whether this polymorphism can be used as a predictive biomarker for identifying resistance development among CML patients undergoing IM treatment.